Analisis dan Perancangan Aplikasi Pendukung Erp Sap R/3 Modul Sales and Distribution PT. United Tractors, Tbk - Johan Johan; Yokie Susanto; Yusmin Joe; Robby Robby (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this research is to analyse sales process having been implementing Sales and Distribution module of ERP SAP R/3 and also to design a supporting application for sales process at PT United Tractor, Tbk. The benefit of this application is to help sales person and customer in doing inquiries, quotation and sales order also material information through short message. The method of this research is data capturing, literature review, object oriented analysis and design and Rational Unified process including UML ( Unified Modeling Language) for application design. Based on the problem, we designed a web based and sms gateway application to support Sales and Distribution module ERP SAP R/3 to help customer and sales person in doing sales transaction and information inquiry.